[Probe Team's third anniversary - Lazaro, Cheche (The Probe Team, 1990)
The Probe Team celebrates its third anniversary with a trip through the year 1989. In a round-table chat with the Apo Hiking Society, they talk about their favorite stories, editorial objectives, bloopers and memorable moments.